Stomach content analysis of Mugil cephalus and Mugil curema (Mugiliformes: Mugilidae) with emphasis on diatoms in the Tamiahua lagoon, México - Sánchez Rueda, Patricia (Universidad de Costa Rica, 2002)
A year-long research on the Mugil cephalus and M. curema diet was conducted. The food content in the cardiac portion of 192 stomachs revealed a great similarity in both species leading to two conclusions: sediments are their basic food and high levels of benthic diatoms are dominant. A total of 130 taxa were found (Nitzschia, Navicula, Amphora, and Cocconeis dominated). Other food components were: Foraminifera, Nematoda, Copepoda, Ostracoda, Amphipoda, Pelecypoda, Gastropoda, eggs of invertebrates, and undetermined organic matter